2020
DOI: 10.3390/nano10081569
|View full text |Cite
|
Sign up to set email alerts
|

Spectral-Time Multiplexing in FRET Complexes of AgInS2/ZnS Quantum Dot and Organic Dyes

Abstract: Nowadays, multiplex analysis is very popular, since it allows to detect a large number of biomarkers simultaneously. Traditional multiplex analysis is usually based on changes of photoluminescence (PL) intensity and/or PL band spectral positions in the presence of analytes. Using PL lifetime as an additional parameter might increase the efficiency of multiplex methods. Quantum dots (QDs) can be used as luminescent markers for multiplex analysis. Ternary in-based QDs are a great alternative to the traditional C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…It was shown that the fluorophore's long lifetimes lead to a considerable suppression of the autofluorescence background and, consequently, to the overall sensitivity improvement [29]. Broad bandwidths and long lifetimes of ternary QDs are also beneficial for the applications with Förster resonance energy transfer (FRET), where QDs can be utilized as efficient energy donors [30][31][32][33]. In this case, the donor−acceptor pairs with acceptor absorption bands overlapping QD PL at different wavelengths and lifetimes result in different lifetimes of sensitized dye PL that allow for spectral and lifetime multiplexing [30,31,34].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was shown that the fluorophore's long lifetimes lead to a considerable suppression of the autofluorescence background and, consequently, to the overall sensitivity improvement [29]. Broad bandwidths and long lifetimes of ternary QDs are also beneficial for the applications with Förster resonance energy transfer (FRET), where QDs can be utilized as efficient energy donors [30][31][32][33]. In this case, the donor−acceptor pairs with acceptor absorption bands overlapping QD PL at different wavelengths and lifetimes result in different lifetimes of sensitized dye PL that allow for spectral and lifetime multiplexing [30,31,34].…”
Section: Introductionmentioning
confidence: 99%
“…Broad bandwidths and long lifetimes of ternary QDs are also beneficial for the applications with Förster resonance energy transfer (FRET), where QDs can be utilized as efficient energy donors [30][31][32][33]. In this case, the donor−acceptor pairs with acceptor absorption bands overlapping QD PL at different wavelengths and lifetimes result in different lifetimes of sensitized dye PL that allow for spectral and lifetime multiplexing [30,31,34]. The combined multiplexing strategy is crucial for creating the next generation bioanalytical sensing platforms and has been a subject of intensive research in the last few years [35,36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important subclass of applications in life sciences employs ternary QDs as energy donors in the complexes with Förster resonant energy transfer (FRET) [ 41 , 42 ]. These complexes might be used for photodynamic therapy [ 43 , 44 , 45 ] and assays for the multiplex analysis [ 46 , 47 , 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, PL lifetimes of ternary QDs are distributed along the emission band with the shorter times at higher energies and the average values of hundreds of nanoseconds [ 10 , 12 , 49 , 50 , 51 ]. Such long wavelength-dependent lifetimes are advantageous for two reasons: (a) they help to separate the short-lived autofluorescence of the biological surroundings, thereby increasing the sensitivity of a sensor [ 46 ]; (b) they allow for lifetime multiplexing—a technique which implies barcoding of luminescent labels based on their lifetimes rather that PL peak positions [ 47 , 48 , 52 , 53 , 54 ].…”
Section: Introductionmentioning
confidence: 99%